Wireless broadcasting retransmission approach based on network coding - XIAO Xiao; WANG Wei-ping; YANG Lu-ming; ZHANG Shuai (Tongxin xuebao)
A novel retransmission approach in wireless broadcasting based on network coding（NCWBR） was presented, the key point of which was to combine different lost packets with network coding to achieve high efficient retransmission.Theoretical analysis reveals that the approach can ensure the solvability in the receiver nodes, and has better retransmission performance.Simulation results indicate that, comparing with existing approach, NWCBR can effectively reduce the average number of transmissions and improve the transmission efficiency.